Antibacterial activity and mechanism of Tetrapleura tetraptera stem extract against Salmonella strains and its application in raw chicken meat. Issue 3 (27th April 2020) - Agyemang, Kwabena; Ofori Donkor, Prince; Ayim, Ishmael; Adzitey, Frederick; Lin, Lin; Cui, Haiying
Abstract: We studied the antibacterial activity and mechanism of Tetrapleura tetraptera stem extract against Salmonella enteritidis and Salmonella typhimurium and its applications in chicken meat. The extract showed significant antibacterial activity in vitro, minimum inhibitory concentration, and minimum bactericidal concentration on the pathogens was found to be 12.5–50.0 mg/ml. The mechanism of action of the T. tetraptera stem on S. enteritidis and S. typhimurium was largely characterized by the changes in the cell integrity, cell membrane permeability which caused the outflow of the intracellular substances such as ATP, DNA, protein, and K + . The extract eventually inhibited bacterial respiratory metabolism through the Embden–Meyerhof–Parnas (EMP) and tricarboxylic acid (TCA) pathways. Furthermore, T. tetraptera showed a significant effect in controlling the growth rate of S. enteritidis and S. typhimurium in meat samples during the 7‐day incubation period, and the surface color and sensory properties were not adversely affected. Practical applications: T. tetraptera is a flowering plant which can be used in local cuisine and traditional medicine. Interestingly, this plant is used in our daily dishes as herbs, spices, seasonings, and preservatives. T. tetraptera stem extract has high antibacterial activity against both gram‐positive and gram‐negative bacteria. This study could contribute to a better understanding of antibacterial activity and the mechanism of T. tetraptera in food. As a preservative for natural foods, it could be used in the meat industry.